LOCAL IRREGULARITY VERTEX COLORING OF BICYCLIC GRAPH FAMILIES - Kristiana, Arika Indah; Santoso, Aji Mansur; Hussen, Saddam; Wihardjo, Edy; Adawiyah, Robiatul; Dafik, Dafik (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
The graph in this research is a simple and connected graph with as vertex set and as an edge set. We used deductive axiomatic and pattern recognition method. Local irregularity vertex coloring is defined as mapping as vertex irregular -labeling and where . The conditions for to be a local irregularity vertex coloring, if with as irregularity vertex labeling and for every . The minimum number of colors produced from local irregularity vertex coloring of graph is called chromatic number local irregularity, denoted by . In this research, we analyze about the local irregularity vertex coloring and determine the chromatic number of local irregularity of bicyclic graphs.